Experimental study on the properties of local coarse aggregate in Sarawak - Chong, Huey Ching (Universiti Malaysia Sarawak, UNIMAS, 2006)
The results of an experimental study on the properties of local coarse aggregate in Sarawak are presented. Three types of coarse aggregate samples were used namely limestone, granite and microtonalite.